Bivalirudin or heparin in primary angioplasty performed through the transradial approach: results from a multicentre registry. Issue 3 (1st September 2014) - Sciahbasi, Alessandro; Rigattieri, Stefano; Cortese, Bernardo; Belloni, Flavia; Russo, Carmelo; Ferraironi, Alessandro; Tespili, Maurizio; Angeletti, Chiara; Ricci, Roberto; Bondanini, Francesco; Pugliese, Francesco Rocco
Abstract: Background: Data on the effect of bivalirudin therapy in primary percutaneous coronary interventions (PCI) performed through the transradial approach are limited. The aim of our study was to evaluate bleeding complications and clinical outcomes in primary PCI performed through the transradial approach with bivalirudin therapy. Methods: We retrospectively evaluated primary PCI performed through the transradial approach from January 2008 to June 2013. Patients were divided in two groups according to the use (group 1) or not (group 2) of bivalirudin. The primary end points were major bleedings and major adverse cardiac events (MACE) within 30 days. Results: During the 5 years analysed, 1009 patients underwent primary PCI through the transradial approach: 154 patients were treated with bivalirudin (males 79%, age 65±14 years) and 855 with heparin (males 82%, 63±12 years). In group 1, the use of glycoprotein IIb/IIIa inhibitors was only 4%, compared to 55% ( p <0.001) in group 2. There were no significant differences between the two groups for major bleedings (0.65% in group 1 and 1.17% in group 2, p =0.88) nor for minor bleedings (1.3% in group 1 and 1.5% in group 2, p =0.83). There were also no significant differences in MACE (7.1% in group 1 and 10.4% in group 2, p =0.27). The 30-day mortality rate was 3.9% in group 1 and 5.4% in group 2 ( p =0.56). Conclusions: In this registry of primary PCI performed through the transradial approach, bivalirudin was not associated with a significant reduction in major bleeding or MACE compared to heparin and provisional glycoprotein IIb/IIIa inhibitors.